Physical geology - Plummer, Charles C.; McGeary, David (Iowa : Wm. C. Brown Publishers, 1996)
Environment Management
Keywords: Physical geology; Volcanism; Metamorphism; Mass wasting; Geologic structure; Earthquakes; Plate tectonics; Geologic resources; Environmental geology